2024
DOI: 10.3389/fvets.2024.1360939
|View full text |Cite
|
Sign up to set email alerts
|

Squid meal and shrimp hydrolysate as novel protein sources for dog food

Joana Guilherme-Fernandes,
Tiago Aires,
António J. M. Fonseca
et al.

Abstract: The world’s growing pet population is raising sustainability and environmental concerns for the petfood industry. Protein-rich marine by-products might contribute to mitigating negative environmental effects, decreasing waste, and improving economic efficiency. The present study evaluated two marine by-products, squid meal and shrimp hydrolysate, as novel protein sources for dog feeding. Along with the analysis of chemical composition and antioxidant activity, palatability was evaluated by comparing a commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Similarly, the CP content and amino acid profile of seafood and crustacean hydrolysates might differ depending on the primary source of protein (species and part of the animal), enzyme source, and hydrolysis conditions ( 17 , 64 ). An earlier study ( 37 ) showed that in shrimp hydrolysate obtained from the enzymatic hydrolysis of heads and cephalothoraxes of Litopenaeus vannamei , as the one used in the current study, lysine and leucine were the essential amino acids found in the highest amounts, and glutamic acid plus glutamine were the main non-essential amino acids. For fish hydrolysates, the review from Chalamaiah, Kumar ( 65 ) reported aspartic acid and glutamic acid to be found in high amounts in most of the fish protein hydrolysates, and that muscle, head, skin, and visceral hydrolysates contain all the essential and non-essential amino acids, whereas in fish frame protein hydrolysates, aromatic amino acids were not reported.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Similarly, the CP content and amino acid profile of seafood and crustacean hydrolysates might differ depending on the primary source of protein (species and part of the animal), enzyme source, and hydrolysis conditions ( 17 , 64 ). An earlier study ( 37 ) showed that in shrimp hydrolysate obtained from the enzymatic hydrolysis of heads and cephalothoraxes of Litopenaeus vannamei , as the one used in the current study, lysine and leucine were the essential amino acids found in the highest amounts, and glutamic acid plus glutamine were the main non-essential amino acids. For fish hydrolysates, the review from Chalamaiah, Kumar ( 65 ) reported aspartic acid and glutamic acid to be found in high amounts in most of the fish protein hydrolysates, and that muscle, head, skin, and visceral hydrolysates contain all the essential and non-essential amino acids, whereas in fish frame protein hydrolysates, aromatic amino acids were not reported.…”
Section: Discussionmentioning
confidence: 74%
“…Although using 20 animals over 2 or 4 days is considered to increase the test resolution ( 36 ), the number of animals used in palatability tests greatly differs in the literature, with studies reporting the use of 8 ( 66 ), 10 ( 67 ), and 16 ( 68 ) animals. In the current study, despite the sample size (12 animals) being defined according to an earlier study that evaluated the dietary supplementation with shrimp hydrolysate ( 37 ), the number of animals used was lower than the generally recommended (20 animals), so some caution should be taken when interpreting the results obtained. Animals accepted well both the control and the experimental diet, with no differences in the first approach, taste, or intake ratio.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Besides the human diet, shrimp hydrolysates also have the potential to be incorporated into petfood. Guilherme-Fernandes et al [215] conducted a study with Beagle dogs to compare a commercial diet with diets incorporating 150 g/ kg of squid meal or shrimp hydrolysate. Based on the results obtained for apparent total tract digestibility, metabolizable energy content, fecal characteristics, metabolites, and microbiota, the authors concluded that squid meal and shrimp hydrolysate could constitute novel and promising protein sources for dog food.…”
Section: Application Of Protein Hydrolysatesmentioning
confidence: 99%